Cambridge guide to mentalization-based treatment (MBT) - Bateman, Anthony 1952-; Fonagy, Peter 1952-; Campbell, Chloe; Luyten, Patrick; Debbané, Martin (Cambridge University Press, 2023)
A complete and practical guide offering a concise overview of mentalization-based treatment (MBT) and its application in different situations and with different groups of patients to help improve the treatment of mental health disorders. Featuring an introduction to mentalizing and the evidence base to support it, followed by the principles of MBT and the basic clinical model in individual and group psychotherapy. Other chapters offer extensive clinical illustrations of the treatment of patients with depression, psychosis, trauma, eating disorders, and borderline, antisocial, narcissistic, and avoidant personality disorders. The final section outlines the application of mentalizing and MBT in different populations – children, adolescents, families, couples – and their use in different contexts – teams, schools, and care settings. Part of the Cambridge Guides to the Psychological Therapies series, offering all the latest scientifically rigorous and practical information on a range of key, evidence-based psychological interventions for clinicians
Keywords: Diseases & disorders / BIC2; Psychiatry / BIC2; Clinical psychology / BIC2